An analysis of disease burden and risk factors of chronic kidney disease in China from 1990 to 2021 - QIN Lihong; CHEN Jing; XIANG Yadie; LI Binghui; LUO Lisha; CHEN Ling (Yixue xinzhi zazhi)
Objective To investigate the current status and trends of chronic kidney disease (CKD) burden in China from 1990 to 2021, and to provide scientific evidence for the formulation of CKD prevention and control policies. Methods Data were sourced from the 2021 Global Burden of Disease Study. The burden of CKD and its subtypes in China was analyzed using incidence, mortality, and disability-adjusted life years (DALY) metrics. The estimated annual percentage change (EAPC) was used to assess the temporal trends. Results In 2021, the age-standardized incidence, mortality and DALY rates of CKD in China were 163.74 per 100,000, 10.84 per 100,000 and 315.33 per 100,000, respectively. From 1990 to 2021, age-standardized incidence rate of CKD showed an upward trend [EAPC=0.52%, 95%CI(0.44, 0.59)], while age-standardized mortality rate [EAPC=-0.90%, 95%CI(-0.98, -0.81)] and age-standardized DALY rate [EAPC=- 1.25%, 95%CI(-1.35, -1.16)] showed downward trends (EAPC